RELASI PIHAK EKSEKUTIF PERUSAHAAN DENGAN KANTOR AKUNTAN PUBLIK DAN PRAKTIK MANAJEMEN LABA - Williem -; Oktavia - (InFestasi, 2019)
This study aims to examine the effect of relations between the executive of the com-pany and Public Accounting Firm, which audits the company, on earnings man-agement practices carried out by the management of the company. The research sample used by this study was 435 observations from manufacturing companies listed on the Indonesia Stock Exchange. The results of this study indicate that the relationship between the executive of the company and KAP which is currently audit the company negatively affects the practice of earnings management. This finding indicates that the practice of earnings management in companies with executives who have worked in public accounting firm that currently audit the companies is actually lower than in companies with executives have never worked in public accounting firm which is currently audit the companies. This research is the first study that measures the relationship between the executive of the company and public accounting firm, by tracing the profile of the company's executive in the annual report of the company or through CV (Curriculum Vitae) in the Google database.